NATURAL RADIOACTIVITY, RADON EXHALATION RATES AND INDOOR RADON CONCENTRATION OF SOME GRANITE SAMPLES USEDACONSTRUCTION MATERIAL IN TURKEY - Turhan, Şeref; Aykamıs, Ahmet S.; Ugur, F.Aysun; Baykan, Umut N.; Kılıç, Ahmet M. (Radiation Protection Dosimetry (2013), pp. 1–7, 2013)
It is very important to determine the levels of the natural radioactivity in construction materials and radon exhalation rate from these materials for assessing potential exposure risks for the residents. The present study deals with 22 different granite samples employed as decoration stones in constructions in Turkey. The natural radioactivity in granite samples was measured by gammaray spectrometry with an HPGe detector. The activity concentrations of 226Ra, 232Th and 40K were found to be in the range of 10–187, 16–354 and 104–1630 Bq kg21, respectively. The radon surface exhalation rate and the radon mass exhalation rate estimated from the measured values of 226Ra content and material properties varied from 1.3 to 24.8 Bq m22 h21 with a mean of 10.5+1.5 Bq m22 h21 and 0.03–0.64 Bq kg21 h21 with a mean of 0.27+0.04 Bq kg21 h21, respectively. Radon concentrations in the room caused from granite samples estimated using a mass balance equation varied from 23 to 461 Bq m23 with a mean of 196+27 Bq m23. Also the gamma index (Ig), external indoor annual effective dose (Eg) and annual effective dose due to the indoor radon exposure (ERn) were estimated as the average value of 1.1+0.1, 0.16+0.02 mSv and 5.0+0.7 mSv, respectively, for the granite samples.
Keywords: NATURAL RADIOACTIVITY, GRANITE SAMPLES